Green collars at the voting booth: Material interest and environmental voting - Enrico Cavallotti; Italo Colantone; Piero Stanig; Francesco Vona (Fondazione Eni Enrico Mattei (FEEM), 2025)
We study how occupation-related material interest affects environmental voting. Specifically, material interest hinges on the greenness vs. brownness of individual occupational profiles. That is, on the extent to which individuals are expected to benefit vs. lose in a greener economy. We employ individual-level data from 14 western European countries, over 2010-2019. To measure the greenness and brownness of occupational profiles, for each individual we compute predicted greenness and brownness scores based on the predicted probabilities to be employed in each possible occupation. These probabilities are combined with occupation-specific greenness and brownness scores. Individuals characterized by higher predicted brownness are less likely to vote for Green parties and for parties with a more environmentalist agenda, while the opposite holds for individuals characterized by higher predicted greenness. Voting preferences of brown profiles tend to converge towards those of greener profiles in regions that are better placed to gain from the green transition.
Keywords: D72; Q52; P16; 330; green voting; material interests; green jobs; brown jobs; labour market effects of the green transition